Exploring the Impact of Emotional Intelligence on Stress Management among College Students of Janakpurdham - Karna, Santosh Kumar (Journal of Nepal Commerce Association, 2025)
The present study aimed to examine the relationship between stress management and emotional intelligence among college students. A total of 200 undergraduate students from University Campus and R. R. M. Campus of Janakpurdham participated in the study. The sample was selected using incidental and purposeful sampling techniques to ensure accessibility and relevance. A cross-sectional research design was adopted, and data were collected using standardized instruments, namely the Emotional Intelligence Scale and the Stress Source Inventory. The collected data were analyzed using appropriate statistical tools through SPSS software. The findings of the study revealed a significant relationship between emotional intelligence and stress management among both male and female students. Results indicated that students with higher levels of emotional intelligence experienced lower levels of stress, while those with lower emotional intelligence reported higher stress levels. This inverse relationship highlights the role of emotional intelligence in effectively managing stress in academic settings. The study concludes that emotional intelligence and stress are negatively correlated, suggesting that enhancing emotional intelligence may serve as a valuable strategy for reducing stress among college students. These findings have important implications for student wellbeing and stress management interventions in higher education institutions.